Edukasi kesehatan “booklet pintar bebas anemia” sebagai upaya pencegahan dan penanganan anemia pada ibu hamil (DEDICATION: Jurnal Pengabdian Masyarakat, 2022)
Abstract One of the complex and global problems is anemia during pregnancy. One of the developing countries with an increasing prevalence of anemia is Indonesia, in the last 5 years, namely 37.1% -48.9%. Efforts that can be made to prevent and treat anemia with health education through booklets. The program carried out is to increase knowledge and awareness of anemia in pregnant women. Counseling activities were carried out at the Bangun Rejo Village Sub-Head Health Center, Dusun VII, Tanjung Morawa District, following the KKN schedule for STIKes Mitra Husada Medan students. The method used in this service is to provide education directly to pregnant women at the Bangun Rejo Village Community Health Center. The results of this activity are carried out in stages from preparation to evaluation. After carrying out health education, there is an increase in knowledge and awareness of pregnant women about anemia, understanding and being able to explain nutritionally balanced and varied foods, being able to mention 3 of the 7 symptoms of anemia in accordance with the material explained, and being able to explain and understand procedures consumption of iron tablets and any drinks that can block the absorption of Fe. Therefore, with this community service project, it is hoped that all pregnant women can increase awareness and fulfill balanced nutrition and nutrition, regularly consume Fe tablets. Furthermore, health workers can promote balanced nutrition through "fill my plate" according to existing regulations. Keywords: booklet, pregnant women, prevention and treatment of anemia